Differentiation Strategy for Firms: Online Ad versus Mass Media Ad - Chieko Fujisawa; Norihiro Kasuga (International Telecommunications Society (ITS), 2022)
This study analyzes advertiser firms' product differentiation strategies and the relationship two media advertising effect, mass media and online media. We derive an inverse demand function from the utility function relating to the evaluation of the goods' additional information that consumers obtain from advertisements, and we analyze the advertising choices of firms using a two-stage decision-making model. The analysis results indicate that firms choose asymmetric advertising to take advantage of the interdependent effects of two advertising and differentiation and to increase profit through rivals' advertising effects. However, the profits of firms are the highest when both firms choose the discriminatory online media advertising. Social welfare is highest in symmetric choice of the discriminatory online advertising, but consumer surplus is highest in symmetric choice of the discriminatory mass media advertising.
Keywords: 330; Online media advertising; Mass media advertising; Targeting; Differentiation Strategy; Interaction